4 Troponin positive acute coronary syndromes and unobstructed coronary arteries: Improved diagnostic and clinical impact by performing cardiovascular magnetic resonance early after presentation. (18th April 2016) - Dastidar, A Ghosh; Rodrigues, J; Johnson, T; De Garate, E; Singhal, P; Baritussio, A; Scatteia, A; Strange, J; Nightingale, A; Baumbach, A; Delgado, V; Bucciarelli-Ducci, C
Abstract : Background: 7–15% of acute coronary syndrome (ACS) patients have unobstructed coronary arteries. In these patients cardiac magnetic resonance (CMR) can identify different underlying aetiologies. Aim: Evaluate the diagnostic and decision making implications of CMR timing (early versus late) in patients with ACS and unobstructed coronary arteries. Methods: 204 consecutive patients (mean age 55yrs, 51% males) with troponin positive ACS and unobstructed coronary arteries, referred for a CMR between September 2011 and July 2014 were evaluated. Comprehensive CMR was performed "early" (≤2weeks from presentation) in 98 patients and "late" (>2weeks from presentation) in 106. "Significant clinical impact" was predefined as change in diagnosis/management. Propensity matching was performed between early and late CMR groups to minimise selection bias. Results: Overall, a cause was found in 70% of patients. CMR had significant clinical impact in 66%, including change in the final diagnosis in 54%. (Figure 1 ) In a multivariable model (included clinical and imaging parameters), presence of late gadolinium enhancement (LGE) and age were the only independent predictors of "significant clinical impact" (LGE OR 2.3, p = 0.02) (Table 1 ). In a propensity score analysis, 58 pair of patients was matched for early and late CMR. The diagnostic pick up rate in the "early" group was significantly higher than in the "late" group (88% vs 50% p < 0.0001). Myocarditis (33%) was the most common diagnosis in the "early" group, whereas myocardial infarction (22%) in the "late" group. The clinical impact also improved significantly in the early group compared to the propensity score matched late group (76% vs 51%, p = 0.01). Conclusion: CMR was able to establish final diagnosis in overall 70%. CMR made significant additive clinical impact on management and diagnosis in 66%, with LGE being the best independent predictor of impact. Moreover, the diagnostic value as well as the clinical impact of CMR was highest when performed early.